Application of a knowledge management tool the web-based manualization of BQE PMO using Google Docs - Tan, Edson R. (University of the Philippines Diliman, 2011)
The BQE Services Project Management Office (PMO) was formed around 2008 to address the need of project management for system integration projects of the company. The PMO adopted the Project Management Institute's (PMI) Framework for managing projects. The framework is an American National Standards Institute (ANSI) standard in the field of project management practice. While using the framework gave the team the needed direction on how projects should be management within the organization, there is has been no document yet on the process of how the projects are actually managed in practice by the members of the PMO. This project was conducted to manualize (put in document from; manual; the development of manuals and guides with technical specifications) the process of project implementation of BQE Services Project Management Organization (PMO). The goal is to be able to explicitly capture, in a form of a manual, the process of project implementation in BQE. An online Knowledge Management (KM) assessment was conducted on the PMO members and its internal clients to determine the needed KM tool to be used on the project. The results of the assessment were analyzed and upon consultation with the PMO Head, the needed KM tool was selected-manualization of the PMO operations or process. Manualization is the documentation of know-how and tacit knowledge of the PMO members on how they implement projects in actual practice. The manual would serve as a guide for the project managers as to how the PMI framework is adapted to the BQE project environment. A web-based manual of operations was created using Google Docs. Furthermore, the manual is made web-based to give it flexibility to accept changes through new knowledge gained by the PMO team members while practicing project management. It contains inputs from the project managers of the PMO based on the PMI framework and how it relates to the actual project management practice in BQE Services. This web-based flexibility is needed in capturing new project-related knowledge as project management involves the actual practice of managing projects rather than a rigid process and continues to evolve over time.